Mechanical Tensile Response of Ni–Graphene Nanocomposites in Hydrogen-Irradiation-Coupled Environments Using Molecular Dynamics Simulations - Tonghe Liu; Xiaoting Yuan; Hai Huang (Nanomaterials, 2025)
In Gen-IV nuclear reactors, structural materials must endure unprecedented levels of neutron irradiation and hydrogen exposure, posing significant challenges for traditional Ni-based alloys. This study evaluates Ni–graphene nanocomposites (NGNCs) as a promising solution, leveraging their inherent radiation tolerance and hydrogen diffusion suppression. Using molecular dynamics simulations, we investigate how Ni/graphene interfaces influence mechanical properties under combined hydrogen permeation and displacement damage. Key parameters, such as hydrogen concentration, displacement damage level, strain rate, and temperature, are systematically varied to assess their impact on stress–strain behavior (including Young’s modulus and tensile strength), with comparisons to single-crystal nickel. Our findings reveal that NGNCs exhibit distinct mechanical responses characterized by serrated stress–strain curves due to interfacial slip. Hydrogen and irradiation effects are complex: low hydrogen levels can increase Young’s modulus, while higher concentrations and irradiation generally degrade strength, with NGNCs being more affected than single-crystal nickel. Additionally, NGNCs show enhanced thermal stability but increased strain rate sensitivity. These results provide critical insights for designing materials that balance reinforcement with environmental resilience in nuclear applications.